A general strategy for development of a single benzene fluorophore with full-color-tunable, environmentally insensitive, and two-photon solid-state emission - Xiang, Zhen; Wang, Zhi-Yao; Ren, Tian-Bing; Xu, Wang; Liu, Yu-Peng; Zhang, Xing-Xing; Wu, Peng; Yuan, Lin; Zhang, Xiao-Bing (Chemical communications (Cambridge, England), 2019)
We report here a single-benzene based fluorescent framework, amino-terephthalonitrile, denoted SB-Fluor . This scaffold displays versatile emission wavelength tunability via structure modification, covering the full visible light spectrum, both in the solution and solid state. Moreover, one molecule, SBF3, exhibits polymorphism-dependent reversible mechanochromic luminescence. We report here a single-benzene based fluorescent framework, amino-terephthalonitrile, denoted SB-Fluor .